2020
DOI: 10.2174/1573398x15666191114144230
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory Role of Vitamin D in Respiratory Diseases

Abstract: : The growing interest in the new role of vitamin D, particularly as an immunomodulatory factor, has spurred basic research and the development of clinical trials to better understand the influence of supplementation on various diseases. Vitamin D is an important nutrient factor in human health due to its role in calcium metabolism regulation, cellular growth, differentiation and its fundamental discovered activity in immune functions. It has influenced different diseases, particularly inflammatory and autoimm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…[21][22][23] Our findings showed a significant association between VDD and respiratory problems, as VD works as an immunomodulator when the level is insufficient and could influence the disease pathophysiology, which is not completely understood. [24] Hence, for the treatment of people infected with COVID-19, higher VD3 doses might be useful. [14] Conversely, our findings showed an opposite significant association between having cardiovascular disease and VDD, which was supported by a recent meta-analysis, as it has been shown that VD supplementation was not associated with reduced major adverse cardiovascular events, individual CVD endpoints (myocardial infarction, stroke, CVD mortality), or all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Our findings showed a significant association between VDD and respiratory problems, as VD works as an immunomodulator when the level is insufficient and could influence the disease pathophysiology, which is not completely understood. [24] Hence, for the treatment of people infected with COVID-19, higher VD3 doses might be useful. [14] Conversely, our findings showed an opposite significant association between having cardiovascular disease and VDD, which was supported by a recent meta-analysis, as it has been shown that VD supplementation was not associated with reduced major adverse cardiovascular events, individual CVD endpoints (myocardial infarction, stroke, CVD mortality), or all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This means that in the case of AR, antihistamines continue and be the cornerstone of treatment with known methods 28,29 and must be accompanied by immunotherapy at the beginning, but as the months pass, it is necessary to try to stop them if the immunotherapy is taken correctly. In this sense, supplementation with vitamin D could be useful since it seems to enhance the effects of SLIT 30,31 . SLIT has proven to be effective in controlling long-term symptoms in the treatment of respiratory allergies, unlike the most common drugs (antihistamines, corticosteroids), which only act on symptoms instead.…”
Section: Discussionmentioning
confidence: 99%
“…This vitamin exerts an anti-infective activity through its ability to favor the synthesis of some peptides with powerful antimicrobial activity (cathelicidin or LL37 protein). It has also been shown that vitamin D intervenes directly in the signaling mechanisms downstream of the T-cell-receptor (TCR) of the T cell, in the maturation of dendritic cells, in the polarization of immune responses, in the promotion of Treg responses, in the production of IgE, and in the recruitment of eosinophils in the airways [ 142 , 143 , 144 , 145 ]. In addition, several human diseases have been associated to vitamin D deficiency and consequently dysregulation in both ROS and Ca2+ signaling.…”
Section: Vitamin Dmentioning
confidence: 99%
“…In the last decade, extraskeletal effects of vitamin D have been discovered which are not directly related to calcium metabolism [142]. It has been documented that, among its many actions, vitamin D enhances the body's immune response: children exposed to recurrent diseases of the airways often have sub-optimal levels of vitamin D (measurable in the blood) and that the correction of the deficit results in an improvement in the state of health and a reduction in the number of infectious episodes [142]. This vitamin exerts an anti-infective activity through its ability to favor the synthesis of some peptides with powerful antimicrobial activity (cathelicidin or LL37 protein).…”
Section: Vitamin Dmentioning
confidence: 99%